A Global Review of Vessel Collisions With Marine Animals - Schoeman, Renée P.; Patterson-Abrolat, Claire; Plön, Stephanie (Frontiers in Marine Science, 2020)
Concern about the effects of maritime vessel collisions with marine animals is increasing worldwide. To date, most scientific publications on this topic have focused on the collisions between large vessels and large whales. However, our review found that at least 75 marine species are affected, including smaller whales, dolphins, porpoises, dugongs, manatees, whale sharks, sharks, seals, sea otters, sea turtles, penguins, and fish. Collision incidents with smaller species are scarce, likely as a result of reporting biases. Some of these biases can be addressed through the establishment of species-specific necropsy protocols to ensure reliable identification of collision related injury, particularly blunt force trauma. In addition, creating a ship strike database for smaller species can assist in identifying the species most frequently involved in collisions, identifying high-risk areas, and determining species-specific relationships between vessel speed and lethal injury. The International Whaling Commission database on collisions with large whales provides a good example of this type of database and its potential uses. Prioritising the establishment of a species-specific necropsy protocol and a database for smaller species as well as the identification of high-risk areas for species other than large whales, would be a valuable step towards the mitigation of collisions with smaller species.